Pregnant Mother's Anxiety During the Covid-19 Pandemic: A Literature Review - Wiji Astuti; Muhammad Syamsu Hidayat (GLOBAL HEALTH SCIENCE GROUP, 2022)
Corona Virus Disease (Covid-19) is a condition that causes illness and death. As of 25 October 2022, it was reported that there were 6.472.664 total confirmed cases and 158.454 deaths in Indonesia. Pregnant women are a high-risk population for Covid-19 infection. During the pandemic, a pregnant woman might be hesitant to attend a health center to monitor her pregnancy for fear of contracting Covid-19. This problem decreased the number of pregnant women in Indonesia who visited health services. This study aims to examine the anxiety issues experienced by pregnant women during the Covid-19 pandemic. This article's methodology was based on an exhaustive search of numerous databases, including PubMed, Scopus, Google Scholar, and the official website. Articles were chosen based on criteria such as free full text, open access, and publication date beyond 2020. The systematic search produced a total of 1238 articles, with 9 articles meeting the inclusion criteria. This research study concluded that pregnant women constitute a high-risk population during the Covid-19 pandemic. Pregnant women were known to feel anxiety in the majority. These psychiatric diseases offer risks to the fetus, including prenatal development impairment, early delivery, and low birth weight. Pregnant women require social assistance to lessen their fear during the Covid-19 pandemic and to increase their compliance with Ante Natal Care.